PA.41 A maternity focused sepsis tool: improving the recognition and management of sepsis in obstetric care. (9th June 2014) - Northridge, R; Hawco, S; Gierasik, L; Knox, S; Lynch, P
Abstract : Introduction: Sepsis is the leading cause of direct maternal mortality, resulting in 27 deaths in the UK between 2006 and 2008: 1 in 70% of these cases, CMACE identified substandard care. 1 The Surviving Sepsis campaign supports early recognition and treatment of sepsis, and improved survival by implementing six evidence based management steps in non-pregnant populations. 2 However, this is not widely used in obstetric care. We aimed to develop and implement a tool utilizing the physiological and biochemical parameters of pregnancy, whilst identifying the clinical features that should raise suspicion of sepsis in this vulnerable group of patients. Methods: Using a trust-wide Sepsis Screening tool, we developed a maternity specific tool. We implemented this throughout our department, and refined it using Plan-Do-Study-Act (PDSA) cycles. Multi-professional education sessions were provided, underlining the importance of prompt management. A retrospective monitoring checklist was devised to audit compliance. Results: Initiation of the bundle between November 2012 and November 2013, improved from 38.5% (5/13 patients) to 100% (13/13 patients). At the beginning of the study only 1/5 women (20%) received the complete bundle within 1 h1 hour, compared to 9/13 (69.2%) in November 2013. Conclusion: The use of a maternity specific sepsis tool prompts early recognition and treatment. We believe our proforma, and ongoing monitoring tool, has raised the profile and awareness of sepsis within our department, resulting in a reduction in time for instigation of the complete bundle. This should result in a reduction in morbidity and mortality in the pregnant population. References: Centre for Maternal and Child Enquiries (CMACE). Saving Mothers' Lives: reviewing maternal deaths to make motherhood safer: 2006–08. The Eighth Report on Confidential Enquiries into Maternal Deaths in the UK. BJOG 2011;118 (Suppl. 1):1–203 Society of Critical Care Medicine. Surviving Sepsis Campaign . [Online] Available from: http://www.survivingsepsis.org/Pages/default.aspx [Accessed 10 th January 2014]